IPv6 Readiness towards Future Internet of Things (IoT) - Main, A.; Zakaria, N.A. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
This paper aims to examine the contribution of IPv6 infrastructure preparedness towards the readiness for IPv6 migration with emphasis on the aspect of physical infrastructure comprises of deployment, equipment and cost. Quantitative study has been carried out by using questionnaire as data collection towards 126 respondents which were network administrators and data has been analyses using regression analysis. Besides, Statistical Package for the Social Sciences (SPSS) version 19 has been used as the tool for data analysis. Findings clearly show that the roles of equipment and deployment, specifically planning, are very important factors that contribute towards the readiness for migration in an organisation. The research undoubtedly shows the contribution and importance of infrastructure aspect in the direction of the IPv6 migration. Therefore top management and policy makers should promote the upgrading of IT infrastructure in their IPv6 roadmap.